Syzgium coriaceum Bosser & J. Guého—An endemic plant potentiates conventional antibiotics, inhibits clinical enzymes and induces apoptosis in breast cancer cells - Mahomoodally, Mohamad Fawzi; Ugurlu, Asli; Llorent-Martínez, Eulogio J.; Nagamootoo, Meenathee; Picot-Allain, Marie Carene Nancy; Baloglu, Mehmet Cengiz; Altunoglu, Yasemin Celik; Hosenally, Muzzammil; Zengin, Gokhan (Elsevier BV, 2020)
Abstract Syzygium species are renowned for being important reservoirs of phytochemicals with pharmaceutical and biomedical potential. However, no attempt has been made to delineate the pharmacological potential and phytochemical profile of Syzgium coriaceum Bosser & J. Gueho, an endemic plant to Mauritius. The present study aimed to determine the antibacterial, antioxidant, cytotoxicity, enzyme inhibitory and phytochemical profile of the ethyl acetate and methanol extracts of S. coriaceum. Preliminary qualitative phytochemical study of the extracts showed the presence of phenol, tannins, and alkaloids. Chemical characterisation showed the presence of derivatives of tannins, gallic acids, quercetin, and kaempferol. Potentiating activity between S. coriaceum extracts and antibiotics (ampicillin and streptomycin) using the checkerboard method showed additive interaction. The extracts showed potent 2,2-diphenyl-1-picrylhydrazyl (DPPH) (2.95 and 2.93 mmol trolox equivalent (TE)/g sample for ethyl acetate and methanol extracts, respectively) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) (4.09 and 3.83 mmol TE/g sample for ethyl acetate and methanol extracts, respectively) scavenging abilities. Syzygium coriaceum extracts were active inhibitors of α-glucosidase (about 47 mmol acarbose equivalent/g sample for ethyl acetate and methanol extract). S. coriaceum methanol extract caused maximum inhibition against human breast adenocarcinoma (MDA-MB-231) cancer cells after 48 h treatment with the IC50 value of 53.41 μg/mL. Expression of anti-apoptotic Bcl2 and BIRC5 genes were down-regulated. It can be concluded that S. coriaceum extracts lead to MDA-MB-231 cells apoptosis. This investigation has provided a comprehensive report of the biological and chemical profile of S. coriaceum. Collected scientific evidences can open new avenues for research and contributes towards establishing primary data on Syzygium species endemic to Mauritius for bioprospection of novel phytopharmaceuticals.
Keywords: Enzyme; Checkerboard; Cytotoxicity; Apoptosis; Phytochemical; Antioxidant; 3. Good health